Seminar “Bersatu Melawan Stunting: Mewujudkan Generasi Emas” Bentuk Edukasi Masyarakat di Desa Kedungjambe oleh Mahasiswa UPN “Veteran” Jawa Timur - Choirunnisa Choirunnisa; Faridatun Nikmah; Grace Salindeho; Hakim Mahdi Zakariya; Mochammad Adam Priyatmoko; Natasha Mardiani Alfons Heyden; Naufal Nur Ahmad; Nia Amalia; Novita Sari Makigawe; Safitri Dwi Ananda; Thalita Rizki Mirzanda Cahyaningrat; Tiara Meyla Seibina; Taufikurrahman Taufikurrahman (Lembaga Pengembangan Kinerja Dosen, 2025)
Stunting is a public health issue that can adversely affect children's growth and future prospects. Stunting poses a threat to the achievement of the second global Sustainable Development Goal (SDG). One effort to address this problem is by providing knowledge to the community about stunting. This effort can be pursued through activities such as stunting seminars. A seminar was held in Kedungjambe Village on November 20, 2024, with the theme